Addressing the quality of higher education among the pandemic in Nueva Ecija, Philippines through the establishment of the community e-learning resource center - Moralde , Rachael Reyes (Journal of Education and e-Learning Research, 2023)
The Community E-learning Resource Center (CeLRC) has enabled faculty members and students to have access to the online facility at higher education institutions in collaboration with the Local Government Units (LGUs) and the Department of Information and Communications Technology (DICT) Tech4Ed centers available in the area. It specifically targets students and faculty members who do not have access to the internet or information and communications technology (ICT) devices such as computer desktops, laptops, tablets and smartphones that support online classes. This study assessed and evaluated the three newly established Community e-Learning Resource Centers in three municipalities in Nueva Ecija, San Isidro, Papaya and Penaranda. A researcher constructed questionnaire and quantitative research design are used. Results showed that the facilities found in three community e-Learning resource centers are safe, secure, functional in every aspect, highly acceptable and comfortable to use. The CeLRC staff is competent and shows a strong sense of interpersonal skills. It is recommended that the results of this study be used by the CeLRC managers to improve the services of the center to ensure its viability, efficacy and efficiency.